PENINGKATAN DAYA SAING PRODUK LOKAL DALAM UPAYA STANDARDISASI MEMASUKI PASAR GLOBAL (STANDARDISASI MUTU DAN KUALITAS UDANG WINDU) - Dananjaya, Irwandaru; Wahyujati, Ajie (Universitas Gunadarma, 2012)
One of the export commodities of the most important fishery and generate a lot offoreign exchange other than tuna fish are shrimp, particularly the type Penausmonodon shrimp have a good comparative competitiveness in internationalmarkets. This condition has resulted in many countries or communities providingraw materials not only tegantung on shrimp fishing in the sea, but also conductan intensive shrimp culture and tend to be large-scale and poorly controlled, withparticular regard to carrying capacity of nature. These activities directly impactthe health of shrimp from several attacks of shrimp diseases, such as bacteria andviruses vibrios. To overcome this illness shrimp farmers were using antibiotics,and even some antibiotics that are prohibited for use in products panganpun alsoencountered in the field, such as CHP and nitrofuran and its derivatives. Theseillicit practices of antibiotic use had a devastating impact on exports of fisheryproducts to the main destination countries, particularly the EU and the U.S.